Looking to the Future: Indigenous Data Sovereignty and Policy in Canada - Paul, Morgan (University of Alberta Library, 2023)
This article explores the concept of Indigenous Data Sovereignty (IDS) in Canada, examining its barriers, resources, implementation, and policy implications. While not an exhaustive list of all IDS-related policies, the article focuses on key definitions, successful implementations, support programs and resources, and outdated policies that hinder IDS and Indigenous governance practices. Through a First Nations lens, the paper highlights the importance of Indigenous People's control over data and knowledge about their communities and lands. It discusses the challenges of implementing IDS within non-Indigenous organizations and communities, including financial constraints and the influence of colonial policies. The article also addresses the impact of IDS on Indigenous self-determination, emphasizing the need for government and educational institutions to support IDS practices. Additionally, it explores the First Nations' principles of Ownership, Control, Access, and Possession (OCAP) as an example of successful IDS implementations. The paper acknowledges the role of data sovereignty in reconciliation frameworks and highlights resources such as the International Work Group for Indigenous Affairs (IWGIA) and the Global Indigenous Data Alliance (GIDA) that advocate for IDS and Indigenous self-governance. The conclusion emphasizes the ongoing need for support, collaboration, and the mobilization of UNDRIP and TRC frameworks to ensure the success of IDS and the amendment of colonial policies.